Relationship between early neural responses to syntactic and acoustic irregularities in music. (14th November 2022) - Ishida, Kai; Nittono, Hiroshi
Abstract: Humans can detect various anomalies in a sound sequence without attending to each dimension explicitly. Event‐related potentials (ERPs) have been used to examine the processes of auditory deviance detection. Previous research has shown that music‐syntactic anomalies elicit early right anterior negativity (ERAN), whereas more general acoustic irregularities elicit mismatch negativity (MMN). Although these ERP components occur in a similar latency range with a similar scalp topography, the relationship between the detection processes they reflect remains unclear. This study compared these components by manipulating music‐syntactic (chord progression) and acoustic (intensity) irregularities orthogonally in two experiments. Non‐musicians (Experiment 1: N = 39; Experiment 2: N = 24) were asked to listen to chord sequences, each consisting of 5 four‐voice chords, as they watched a silent video clip. Standard, harmonic‐deviant, intensity‐deviant and double‐deviant chords occurred at the final position in each sequence. Deviant stimuli were presented infrequently ( p = .10) in Experiment 1 and equiprobably ( p = .25) in Experiment 2. Regardless of deviance probability, both harmonic and intensity deviants elicited similar negativities, which were indistinguishable in terms of latency or scalp distribution. When the two deviant types occurred simultaneously, the negativity increased in an additive manner; that is, the amplitude of the double‐deviant ERP was as large as the sum of the single‐deviant ERPs. These findings suggest that the detection of music‐syntactic and acoustic irregularities works independently, based on different regularity representations. Abstract : In two passive‐listening experiments, the relationship between the detection processes of music‐syntactic and acoustic regularities was examined by presenting instances of harmonic and intensity deviants independently (single deviant) or simultaneously (double deviant). The harmonic and intensity deviants elicited early negativity with similar latency and topography; an additive effect was observed when both deviants co‐occurred. The results suggest that music‐syntactic and acoustic irregularities are detected independently, based on different and independent representations.